Evolution of human diseases - harem othman smail (International Journal of Applied Biology, 2020)
The main aims of this review were to understand the roles of evolutionary process in human disease. The suffering of human from disease may be millions years ago and until now are continuing and the human disease can be classified into many types based on their sources such as bacterial, Genetics and viral. For the past sixty years the scientist carried out high number of experiment to understand   and the decision of the evolutionary process impact of the human disease. the main example of effect of evolution on the human health are using overuse of antibiotics against bacterial infection   and the results to the speedy evolution of bacteria that are resistant to multiple antibiotics such that even vancomycin. The process of natural selection which is proposed by Charles Darwin play vital roles in Biological and medical process and also helps to predict and find the relationship between natural selection process of evolution and phenotypical traits. Understanding the developmental and genetic underpinnings of unique evolutionary changes have been hindered by way of insufficient databases of evolutionary anatomy and through the lack of a computational method to become aware of underlying candidate genes and regulators to the developing o the process of the evolution with helps of other branches of modern sciences such as genetics, Bioinformatics, epidemiology, ecology, microbiology, molecular biology and biochemistry.